Metabolomics study of cured tobacco using liquid chromatography with mass spectrometry: Method development and its application in investigating the chemical differences of tobacco from three growing regions. Issue 9 (19th March 2014) - Li, Lili; Zhao, Chunxia; Chang, Yuwei; Lu, Xin; Zhang, Junjie; Zhao, Yanni; Zhao, Jieyu; Xu, Guowang
<x xml:space="preserve">Abstract</x> Cured tobacco is an important plant material. Component studies are a big challenge for its significantly diverse chemical properties and vastly different concentrations. In this work, liquid chromatography with quadrupole time‐of‐flight mass spectrometry was used to perform a metabolomics study of cured tobacco owing to its efficient separation and detection of semipolar metabolites. A solvent of methanol/water (8:2, v/v) and 30 min of ultrasound time were found to be optimal to perform extraction. 95, 92, and 93% of metabolite features had within 20% of coefficient of variation for repeatability, intraday and interday precision analysis, respectively, indicating a good stability of the method developed. 113 metabolites were identified in cured tobacco based on accurate mass, retention time, and MS/MS fragments. The developed method was applied to a metabolomics study of cured tobacco from three growing regions. Forty three metabolites were found to be contributed to the classification. It is shown that the developed method can be applied to metabolomics analysis of plant materials.